O uso de uma rede social gamificada para o ensino de língua estrangeira - Carvalho, Paula Marcia Bonsegno (2015)
This research presents the use of gamification for learning and teaching a foreign language in a social networking environment. The research problem of the dissertation is to investigate how a gamified social networking can be constituted as an environment for learning a foreign language. The objective of this research was to identify the game´s elements present in the social networking Busuu and verify if gamification can be an engaging experience in the learning and teaching process of a foreign language. The authors based the research are: Anderson (2007, 2008), Boyd e Ellison (2007), Carolei (2012, 2015), Henri e Pudelko (2003), Hessel (2012), Huizinga (1971), Kapp (2012), Karpati (2009), Levy (1999), Mattar (2013, 2014), McGonigal (2011),McLoughlin & Lee (2007), O´Reilly (2005, 2009), Recuero (2004, 2009), Salen e Zimmerman (2012), Vianna (2013), Warschauer (1996,1998) Wenger (1998), Werbach & Hunter (2012), Zichermann e Cunningham (2011), Zourou (2012, 2013). The methodology used is part of the typology of Social Research with a qualitative approach and contemplated the creation of a database with the data collected of a questionnaire. As the survey results, it is noted that the game´s elements present in the context of Social Networking Site for Language Learning, when carefully used, enable an environment for teaching and learning a foreign language, favoring a possibility of communication in authentic contexts, engaging users in collaborative activities and generating interest in their learning. Therefore, this dissertation brings to reflection the educational potential in the environment present of a gamified social network and how such technologies can enable new and different ways of constructing knowledge in foreign language